2004
DOI: 10.1523/jneurosci.4521-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Dendritic Elaboration of Sensory Neurons inDrosophila: Insights fromIn VivoTime Lapse

Abstract: In vivo time-lapse multiphoton microscopy was used to analyze the remodeling of the dendritic arborizing (da) sensory neuron known as dorsal dendritic arborizing neuron E (ddaE) during metamorphosis. After its larval processes have been removed, the cell body of ddaE repositions itself on the body wall between 25 and 40 hr after puparium formation (APF) and begins its adult outgrowth at 40 hr APF. The scaffold of the arbor is laid down between 40 and 54 hr APF, when growth is characterized by high filopodial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 39 publications
3
65
0
1
Order By: Relevance
“…The abdominal sensory system of the adult fly is a mosaic consisting of postembryonic neurons derived from the imaginal histoblast nests and genital disk (Hartenstein and Posakony, 1989;Taylor, 1989), and a subset of larval sensory neurons of embryonic origin (Williams and Shepherd, 1999;Williams and Truman, 2004). At the onset of metamorphosis, larval sensory neurons either die or survive and remodel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominal sensory system of the adult fly is a mosaic consisting of postembryonic neurons derived from the imaginal histoblast nests and genital disk (Hartenstein and Posakony, 1989;Taylor, 1989), and a subset of larval sensory neurons of embryonic origin (Williams and Shepherd, 1999;Williams and Truman, 2004). At the onset of metamorphosis, larval sensory neurons either die or survive and remodel.…”
Section: Discussionmentioning
confidence: 99%
“…Among those that survive are dendritic arborizing (da) sensory neurons (Usui-Ishihara et al, 2000;Williams and Shepherd, 2002). The large, complex dendritic arbors of these neurons are completely removed during early metamorphosis, before the cells elaborate their adult-specific arbors (Smith and Shepherd, 1996;Williams and Truman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In holometabolous insects, dendritic regression is dependent on hormonal cues (Weeks et al, 1992;Weeks, 1999;Williams and Truman, 2004). Manduca proleg motoneurons are one of the rare systems in which it has been shown that dendritic retraction is accompanied by synapse elimination and, thus, the dismantling of larval motor circuits (Streichert and Weeks, 1995;Gray and Weeks, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…After an initial phase of slow dendrite growth, rapid extension and arborization occurs, characterized by an increased rate of additions and retractions of branches (Wu et al, 1999;Williams and Truman, 2004) and high motility of filopodia on dendritic growth cones (Portera-Cailliau et al, 2003;Williams and Truman, 2004). Subsequently, the dendritic arbor becomes more stable, showing a reduced rate of branch additions and retractions (Wu et al, 1999) and disappearance of growth cone-associated filopodia (PorteraCailliau et al, 2003).…”
Section: Pi3k In Stages Of Dendrite Developmentmentioning
confidence: 99%